Tackling the Waves of COVID-19: A Planning Model for Intrahospital Resource Allocation - Schmidt, Felicitas; Hauptmann, Christian; Kohlenz, Walter; Gasser, Philipp; Hartmann, Sascha; Daunderer, Michael; Weiler, Thomas; Nowak, Lorenz (Frontiers in Health Services, 2021)
Background: The Corona pandemic requires hospitals to ensure care not only for Covid-19 patients and resources must be allocated accordingly. Objective: To provide hospitals with a planning model when to allocate resources to ICUs given a certain incidence of COVID-19 cases. Methods: The analysis included 334 cases from four adjacent counties south-west of Munich. From length of stay and type of ward (NOR (general ward), ICU) probabilities of case numbers within a hospital at a certain time point were derived. The epidemiological situation was simulated by the effective reproduction number R, the infection rates in mid-August 2020 in the counties and the German hospitalization rate. Simulation results are compared with real data from 2nd and 3rd wave (September 2020 – May 2021). Results: With R = 2, a hospitalization rate of 17%, mitigation measures implemented on day 9 (7-day incidence surpassing 50/100,000), the peak occupancy was reached on day 22 (155.1 beds) for NOR and on day 25 (44.9 beds) for ICU. A higher R lead to higher occupancy rates, however, with an elongated period to peak occupancy and thus an extended preparation time. Simulated number of infections and ICU occupancy fit well with real data obtained from 2nd and 3rd wave. Conclusion: Hospitals could expect a peak NOR and ICU within approximately 5 to 11 days after infections reached their peak and critical resources could be allocated accordingly. This delay (in particular for the peak of ICU occupancy) might give options to get prepared early enough, e.g. by preparing additional ICU resources.